Del testimonio al activismo: la dimensión política de la novela gráfica sobre emigración - Potok, Magda (Studia Romanica Posnaniensia, 2026)
This article examines the political dimension of three Spanish graphic novels – La grieta (Spottorno & Abril, 2016), Asylum (Isusi, 2017), and El cielo en la cabeza (Altarriba, García & Moral, 2023) – focused on forced migration. Drawing on theories of visual testimony, representation ethics, and political imagination, it explores how sequential art moves from documenting trauma to actively denouncing structural violence and reshaping public discourse. Through visual metaphors, chromatic symbolism, photographic integration, testimonial narration, and experimental panel composition, these works build a poetics of displacement that fosters emotional and ethical reader engagement. The study argues that such formal strategies create an ethics of reception that transforms readers into active participants rather than passive spectators. Ultimately, the comics not only critique European border regimes but also propose alternative solidarities, linking Spain’s memory of exile with present-day South-North migration routes.